COVID-19 among the inhabitants of the slums in the city of Buenos Aires: a population-based study. Issue 1 (20th January 2021) - Macchia, Alejandro; Ferrante, Daniel; Battistella, Gabriel; Mariani, Javier; González Bernaldo de Quirós, Fernán
Abstract : Objective: To summarise the unfolding of the COVID-19 epidemic among slum dwellers and different social strata in the city of Buenos Aires during the first 20 weeks after the first reported case. Design: Observational study using a time-series analysis. Natural experiment in a big city. Setting: Population of the city of Buenos Aires and the integrated health reporting system records of positive RT-PCR for COVID-19 tests. Participants: Records from the Argentine Integrated Health Reporting System for all persons with suspected and RT-PCR-confirmed diagnosis of COVID-19 between 31 January and 14 July 2020. Outcomes: To estimate the effects of living in a slum on the standardised incidence rate of COVID-19, corrected Poisson regression models were used. Additionally, the impact of socioeconomic status was performed using an ecological analysis at the community level. Results: A total of 114 052 people were tested for symptoms related with COVID-19. Of these, 39 039 (34.2%) were RT-PCR positive. The incidence rates for COVID-19 towards the end of the 20th week were 160 (155 to 165) per 100 000 people among the inhabitants who did not reside in the slums (n=2 841 997) and 708 (674 to 642) among slums dwellers (n=233 749). Compared with the better-off socioeconomic quintile (1.00), there was a linear gradient on incidence rates: 1.36 (1.25 to 1.46), 1.61 (1.49 to 1.74), 1.86 (1.72 to 2.01), 2.94 (2.74 to 3.16) from Q2 to Q5, respectively. Slum dwellers were associated with an incidence rate of 14.3 (13.4 to 15.4). Conclusions: The distribution of the epidemic is socially conditioned. Slum dwellers are at a much higher risk than the rest of the community. Slum dwellers should not be considered just another risk category but an entirely different reality that requires policies tailored to their needs.